Inside Review Of Gramya Ahara(Unwholesome Dietary factors) In Ayurveda - Sharma, Preeti; Vashistha, Namit (International Research Journal of Ayurveda & Yoga, 2021)
With the advancement in medical facilities and health awareness, though the communicable diseases have come under control, there is an upsurge in the non- communicable diseases. Even though lots of research works are carried out on dietary habits, lifestyle and psychological factors in manifestation of Metabolic Syndrome but there is no holistic approach in studying them under one heading. Ayurveda emphasizing on holistic approach in the diagnosis and treatment principles has given faulty dietary and lifestyle habits under one heading called Gramya Ahara (unwholesome dietary habits) As for the prevention of the metabolic syndrome so there is need to understand the concept of Gramya Ahara(Unwholesome dietary habits).